La monnaie canadienne : 400 ans d’histoire - Lemay, Nicole (Assurances, 1986)
To mark the 75th anniversary of l'École des Hautes Études Commerciales of Montreal, the Celebrations Committee organized, among others, an exposition of currencies used in Canada since its early days. Having received authorization from the author, the HEC and the Celebrations Committee, we are publishing numerous extracts from the special issue of HECHANGES, devoted to the various currencies first used by American Indians, then the early settlers of the French colony. These include commodity money, coins, paper money, notes (under the British Regime), tokens and, lastly, today's currency. Although we could not reproduce the currencies featured in the exposition, we did obtain the authorization to present the texts describing each currency. We express our thanks to the HEC and to the author, Mrs. Nicole Lemay, to whom we are grateful for allowing us to publish her study.